2021
DOI: 10.3389/fpsyg.2021.731244
|View full text |Cite
|
Sign up to set email alerts
|

Novel Evidence for the Increasing Prevalence of Unique Names in China: A Reply to Ogihara

Abstract: In this study, we aimed to address three comments proposed by Ogihara on a recent study where we found that unique names in China have become increasingly popular from 1950 to 2009. Using a large representative sample of Chinese names (N = 2.1 million), we replicated the increase in uniqueness of Chinese names from 1920 to 2005, especially since the 1970s, with multiple uniqueness indices based on name-character frequency and name-length deviation. Over the years, Chinese characters that are rare in daily life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(41 citation statements)
references
References 13 publications
(37 reference statements)
0
24
0
Order By: Relevance
“…Indeed, their study showed that most (39 out of 53) of the countries they examined indicated a substantial increase in individualistic values, whereas only five countries (China, Armenia, Croatia, Ukraine, and Uruguay) exhibited a nonnegligible decrease in individualistic values. 2 However, these words increased in frequency only slightly. As the authors emphasized in their article, the contrasting individualistic words ("choose" and "get") that were analyzed increased more remarkably (for the details of their interpretation, see Zeng and Greenfield, 2015).…”
Section: Decrease In Individualism In Chinamentioning
confidence: 93%
See 2 more Smart Citations
“…Indeed, their study showed that most (39 out of 53) of the countries they examined indicated a substantial increase in individualistic values, whereas only five countries (China, Armenia, Croatia, Ukraine, and Uruguay) exhibited a nonnegligible decrease in individualistic values. 2 However, these words increased in frequency only slightly. As the authors emphasized in their article, the contrasting individualistic words ("choose" and "get") that were analyzed increased more remarkably (for the details of their interpretation, see Zeng and Greenfield, 2015).…”
Section: Decrease In Individualism In Chinamentioning
confidence: 93%
“…Not only values but also behaviors may have become more individualistic. It has been claimed that unique names increased in China between 1950 and 2009, suggesting a rise in the need for uniqueness and individualism (Cai, Zou, Feng, Liu, & Jing, 2018;Bao, Cai, Jing, & Wang, 2021; but also see, Ogihara, 2020b).…”
Section: Increase In Individualism In Chinamentioning
confidence: 99%
See 1 more Smart Citation
“…For example, revealing how people in Japan give names to babies enables comparisons with naming practices in other countries in the Sinosphere. Indeed, such a comparison shows substantial cultural differences and similarities in naming practices between Japan and China (e.g.,Ogihara, 2020b;Bao et al, 2021), which deepens our understanding of naming behaviors, languages, and cultures.…”
mentioning
confidence: 99%
“… 1 I have conducted several studies on Han Chinese names, including one that confirms the increasing prevalence of unique names in China over 1920 to 2005 (Bao et al, 2021). 2 I also have carefully read the original article by Stojcic et al (2020), the correspondence by Ogihara, and the other two reviewers’ insightful comments on this correspondence. In general, I agree with the two points proposed by Ogihara as well as most of the other two reviewers’ opinions.…”
mentioning
confidence: 99%